2000
DOI: 10.1097/00001756-200005150-00031
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral neglect induced by right posterior parietal rTMS in healthy subjects

Abstract: This study demonstrates the neural system potentially involved in the representation of, and choice between, stimulus classifications in an ambiguous, novel, decision-making task. This difficult choice behaviour is taken as an example of a basic executive processing task. Subjects heard sounds that were consonant-vowel combinations that had been distorted and were required to categorize each stimulus as speech-like or not-speech-like. Cerebral activity was measured with positron emission tomography. A neural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
98
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 8 publications
17
98
0
3
Order By: Relevance
“…effects that last as long as 50 ms after the single pulse) at the cortical level induced by single-pulse TMS [27,28]. Our results are consistent with a previous TMS study [15] showing it is possible to interfere with visuo-spatial processing by stimulating the right PPC although repetitive TMS and different parietal zones of stimulation (P5 and P6 instead of P3 and P4 in the present study) were used in this earlier experiment.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…effects that last as long as 50 ms after the single pulse) at the cortical level induced by single-pulse TMS [27,28]. Our results are consistent with a previous TMS study [15] showing it is possible to interfere with visuo-spatial processing by stimulating the right PPC although repetitive TMS and different parietal zones of stimulation (P5 and P6 instead of P3 and P4 in the present study) were used in this earlier experiment.…”
Section: Discussionsupporting
confidence: 89%
“…Here we showed that single-pulse TMS applied over the right PPC mainly corresponding to BA7 is able to selectively interfere with visuo-spatial processing at an early stage (50 ms poststimulus). The use of the TMS±MRI co-registration algorithm indicated that stimulations in the right (P4) and left (P3) PPC do not overlap the post-central gyrus, as previously suggested by others [13,15].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Right parietal repetitive (r)TMS induces a rightward bias in judgments about the symmetry of prebisected lines, which mimics the rightward error in line bisection, committed by right-brain-damaged patients with left neglect; left parietal rTMS, by contrast, has no detectable effects on this task [43,44]. rTMS of the left or of the right parietal lobe produces visual extinction of contralateral stimuli during double simultaneous stimulation [45].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%